Gastrointestinal stromal tumor of the pancreas: A case report and review of the literature - Trabelsi, Amel (Medknow Publications & Media Pvt Ltd, 2009)
CONTEXT: Primary stromal tumors of the pancreas are extremely rare. Only four cases have been reported in the literature. We describe a new case and analyze, through a review of the literature, the clinical and pathological data, and the outcome of the previously reported cases. CASE REPORT: We report the case of a 52-year-old-woman who presented with epigastric pain. Preoperatively, abdominal pelvic computed tomography revealed a pancreatic head mass. The surgery confirmed the presence of a large tumor of the pancreatic head. Pathologic results revealed a malignant gastrointestinal stromal tumor of the pancreatic head, completely removed. There is no recurrence or metastases 10 months after surgery. CONCLUSION: The current case consolidates the possibility that this rare tumor can involve the pancreas as a primary site and that GIST of primary pancreatic localization are usually of high risk of malignancy.